Evaluation of Facilities Improvement and Utilization Strategy Tegal Port - Awel Suryadi; Fuad Ardani Rahman (Politeknik Ilmu Pelayaran Semarang, 2023)
According to the national port master plan, Tegal Port is a hub port. In practice, a number of fishing boats crowd the port pool area thereby disturbing the area that should be used for the port loading and unloading process. Full port facilities are not supported by this circumstance. Commercial ships wishing to enter the port must wait for the tide to enter the waters of the port pool because shipping lanes enter the port wisely around 3 LWS. This study aims to examine the relationship between the port facility utilization index and the port facility performance index in several categories of capacity accessibility and satisfactory performance levels, in the categories of safety, order, smoothness and speed, and pollution experienced unsatisfactory performance. This research uses a descriptive method. Data obtained from surveys and analyzed using the SWOT method. The SWOT analysis shows strength-opportunity (SO) conditions where managers must maximize the potential of ports that have facilities. The results of the SWOT analysis show that the right strategy to use for port development is strength-opportunity, namely improving existing facilities as well as possible, such as making repairs to facilities that are not suitable for use and adding facilities at the port and increasing cooperation with stakeholders by making more work agreements, promising and facilitating service users as well as cutting bureaucracy that does not complicate service users.